Pengaruh Penerapan Good Corporate Governance Dan Efektivitas Audit Internal Terhadap Kualitas Laporan Keuangan Di Organisasi Pemerintah Daerah Kabupaten Ende, Nusa Tenggara Timur - Harjito, Yunus; Gete, Oktaviani Theodora; Sugiarti, Sugiarti (Jurnal Bisnis dan Kewirausahaan, 2022)
The purpose of this study to determine the effect of the implementation of good corporate governance and internal audit effectiveness on the quality of financial reports in the regional government organization of Ende Regency, East Nusa Tenggara, either partially or simultaneously. The population in this research are all staff/employees who work in local government organizations, especially the finance department. There are 32 registered Regional Government Organizations (OPD). The sample obtained and used in the study was 75 respondents. The sample was selected using a sample selection technique, namely Purposive Sampling. The method used is Multiple Linear Regression The results of the study are: Good Corporate Governance has a significant positive effect on the Quality of Financial Statements, Internal audit has a positive effect on the Quality of Financial Reports